Resourcefulness in higher education in the context of lifelong learning in a situation of a change - Szerląg, Alicja (Pedagogika, 2013)
Europeanisation, demanded by the civilization progress, locates the educational discourse within the IT society, which in turn formulates expectations towards the quality of the human capital strengthened by higher education. As a result, it is expected from the graduates to possess competences basing on innovativeness and creativeness, hence – resourcefulness. However, traditionally accomplished process of educating students does not orient towards such competences. Therefore, it is necessary to change the model of academic education. The aim of this article is to indicate the conditions of shaping European model of education in higher education, and in consequence – the range and quality of competences acquired by students. The learning outcomes corresponding with the European directives, particularly in the context of lifelong learning were relevant in these reflections.